Strategi Pemasaran Pt Wika Industri Manufaktur dalam Meningkatkan Penjualan Produk Motor Listrik - Bimafaazaa Athallah Veva; Raden Roro Ratna Roostika (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
PT WIKA Industri Manufaktur is a company operating in the automotive sector in Indonesia. The products sold by PT WIMA are the GESITS G1 and GESITS RAYA G electric motorbikes. The company must have an effective and efficient strategy in selling new electric motorbike products in Indonesia. This research aims to determine the implementation of marketing strategies carried out by PT WIMA. This research uses a qualitative approach by conducting interviews and collecting data from several parties involved in the PT WIMA marketing program. Through data collection using observation methods, it can be seen that the marketing strategy carried out by PT WIMA in marketing GESITS electric motorbikes is to use the Segmenting, Targeting, Positioning (STP) marketing strategy and also the 4P Marketing Mix strategy (Product, Price, Promotion, Place)